(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article presents the causal relationships between the health of workers and the process of urbanization. It is proved that the health of workers in the conditions of urbanization is subject to the negative effects of environmental pollution, lifestyle, nature of the work. Attention is focused on such specific impacts of urbanization on health as an obesity (on the sedentary work workers) and occupational diseases, occupational injuries (on the production workers). Identify trends to an increase the incidence in the whole world, and in Ukraine. Proposed management measures to mitigate negative impact of urbanization and addressing the problem of ensuring the health of workers, which involves complex actions of the state, employers, each employee based on a consolidated social responsibility: environmental education, productive employment, sustainable urban development, healthy lifestyle, access to quality medicine.